Emerging investigator series: radium accumulation in carbonate river sediments at oil and gas produced water discharges: implications for beneficial use as disposal management. Issue 2 (30th November 2018) - McDevitt, Bonnie; McLaughlin, Molly; Cravotta, Charles A.; Ajemigbitse, Moses A.; Van Sice, Katherine J.; Blotevogel, Jens; Borch, Thomas; Warner, Nathaniel R.
Abstract : In the western U.S., produced water from oil and gas wells discharged to surface water augments downstream supplies used for irrigation and livestock watering. Abstract : In the western U.S., produced water from oil and gas wells discharged to surface water augments downstream supplies used for irrigation and livestock watering. Here we investigate six permitted discharges on three neighboring tributary systems in Wyoming. During 2013–16, we evaluated radium activities of the permitted discharges and the potential for radium accumulation in associated stream sediments. Radium activities of the sediments at the points of discharge ranged from approximately 200–3600 Bq kg −1 with elevated activities above the background of 74 Bq kg −1 over 30 km downstream of one permitted discharge. Sediment as deep as 30 cm near the point of discharge had radium activities elevated above background. X-ray diffraction and targeted sequential extraction of radium in sediments indicate that radium is likely coprecipitated with carbonate and, to a lesser extent, sulfate minerals. PHREEQC modeling predicts radium coprecipitation with aragonite and barite, but over-estimates the latter compared to observations of downstream sediment, where carbonate predominates. Mass-balance calculations indicate over 3 billion Bq of radium activity ( 226 Ra + 228 Ra) is discharged each year from five of the discharges, combined, with only 5 percent of the annual load retained in stream sediments within 100 m of the effluent discharges; the remaining 95 percent of the radium is transported farther downstream as sediment-associated and aqueous species.